Impact of Dairying on Livelihood Security of Dairy Farmers in Aspirational Districts of Karnataka - Somasekaran , Subash; K M, ABHISHEK; MCA, DEVI; Muniandy, Sivaram (Indian Journal of Dairy Science, 2025)
This study examines the socio-economic impact of dairying on the livelihood security of farmers in the Aspirational districts of Karnataka, viz., Raichur and Yadgir districts. Dairying is a vital component of rural economies, contributing significantly to food security and poverty alleviation. Livelihood Security Index (LSI) was constructed to assess the differences between dairy and non-dairy farmers across seven dimensions; food and nutritional security, economic security, health security, educational security, social security, institutional security, and infrastructural security. Findings indicate that dairy farmers enjoy higher LSI compared to their non-dairy counterparts, attributed to consistent income generation and better integration into support systems. The study also highlights essential management practices adopted by dairy farmers, including housing, feeding, health care, breeding, and milking techniques. These practices were crucial for enhancing productivity and profitability in the dairy sector. The research underscores the importance of promoting dairying as a sustainable livelihood strategy to improve the rural livelihoods of farmers, especially in Aspirational districts of our country.